2018
DOI: 10.20944/preprints201811.0381.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of High Positive Autocorrelation on the Performance of Garch Family Models

Abstract: This study compared the performance of five Family Generalized Auto-Regressive Conditional Heteroscedastic (fGARCH) models (sGARCH, gjrGARCH, iGARCH, TGARCH and NGARCH) in the presence of high positive autocorrelation. To achieve this, financial time series was simulated with autocorrelated coefficients as ρ = (0.8, 0.85, 0.9, 0.95, 0.99), at different time series lengths (as 250, 500, 750, 1000, 1250, 1500) and each trial was repeated 1000 times carried out in R environment using rugarch package. And … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
5
0
0
Order By: Relevance
“…Using Akaike Information Criterion (AIC) the eGARCH outperformed other models for normal innovation while for student t innovation; the NGARCH model outperformed other models. The performance of NGARCH is in line with the work of Emenogu and Adenomon (2018). The the descriptive statistics of the cleansed retuns of total Nigeria , Plc in table 4 table above also exhibits the characteristics of financial time series.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Using Akaike Information Criterion (AIC) the eGARCH outperformed other models for normal innovation while for student t innovation; the NGARCH model outperformed other models. The performance of NGARCH is in line with the work of Emenogu and Adenomon (2018). The the descriptive statistics of the cleansed retuns of total Nigeria , Plc in table 4 table above also exhibits the characteristics of financial time series.…”
Section: Resultssupporting
confidence: 72%
“…The mean-reverting number of day for the returns of Total Nigeria plc differs from model to model. The performance of NGARCH is in line with the work of Emenogu and Adenomon (2018). Evidence from the VaR Analysis revealed from the selected models revealed that the Risk of VaR losses is high at 99% confidence level, slightly high at 95% confidence level and better at 90% confidence level.…”
Section: Conclusion and Recommendationssupporting
confidence: 72%
“…Using the Akaike information criterion (AIC), the eGARCH outperformed the other models for normal innovation, while, for student t innovation, the NGARCH model outperformed the other models. The performance of NGARCH was found to be in line with the work of Emenogu and Adenomon (2018). Table 3 shows the persistence and half-life volatility of the models.…”
Section: Resultssupporting
confidence: 69%
“…The mean-reverting number of day for the returns of Total Nigeria Plc differed from model to model. The performance of NGARCH was in line with the work of Emenogu and Adenomon (2018). Evidence from the VaR analysis of the selected models revealed that the risk of VaR losses was high at a 99% confidence level, slightly high at a 95% confidence level and better at a 90% confidence level.…”
Section: Conclusion and Recommendationssupporting
confidence: 67%
“…A study on the gold return volatility demonstrated that FIGARCH, which incorporated a long memory process, outperforms other models (Bentes, 2015;. Similar findings were documented by Emenogu et al, (2018); Slim et al, (2017). These studies also showed that accounting for asymmetry is equally essential, especially while studying emerging economies.…”
Section: Literature Reviewsupporting
confidence: 53%